2008
DOI: 10.1016/j.virol.2007.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Circularization of an RNA template via long-range base pairing is critical for hepadnaviral reverse transcription

Abstract: Although an overall genetic strategy for hepadnaviral reverse transcription has been established, the mechanism that underlies the minus-strand transfer is still poorly defined. We and others independently identified a novel cis-acting element, termed beta or varphi, respectively, that is critical for the minus-strand DNA synthesis of hepatitis B virus. A 5'-3', long-range interaction of the RNA template was proposed that involves the 5' epsilon sequence (encapsidation signal) and the 3' beta/varphi sequence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…2 demonstrated that HBV Pol could interact with DDX3 in the absence of the pgRNA. Following the incorporation of DDX3 into the nucleocapsid (hexagon), DDX3 inhibits viral reverse transcription, perhaps disrupting a secondary structure of the pgRNA that is necessary for viral genome replication (1,28,36). Nucleocapsids assembled with DDX3 represent the replication-incompetent particles (A), whereas nucleocapsids assembled without DDX3 represent the replication-competent particles that can execute viral reverse transcription (B).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2 demonstrated that HBV Pol could interact with DDX3 in the absence of the pgRNA. Following the incorporation of DDX3 into the nucleocapsid (hexagon), DDX3 inhibits viral reverse transcription, perhaps disrupting a secondary structure of the pgRNA that is necessary for viral genome replication (1,28,36). Nucleocapsids assembled with DDX3 represent the replication-incompetent particles (A), whereas nucleocapsids assembled without DDX3 represent the replication-competent particles that can execute viral reverse transcription (B).…”
Section: Discussionmentioning
confidence: 99%
“…3A), suggesting a defect in minus-strand DNA synthesis, which is the first step of reverse transcription. We speculated that a secondary structure arising during the minus-strand DNA synthesis, such as one involving base pairing between the 5Ј ε sequence and the 3Ј ⌽ sequence, might be the target for DDX3 (1,28,36). To determine the actual target of DDX3, further investigation is needed to uncover the exact step of viral reverse transcription in which DDX3 interferes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pT7 m -HBV construct that was used to generate the cap-free RNA was described previously (10). The HBV Pol-null construct that was made by an introduction of a frameshift mutation in the Pol gene was previously described (22). The plasmid constructs encoding eIF4E, eIF4E-W73A, and 4E-BP were the generous gift of N. Sonenberg (McGill University).…”
Section: Methodsmentioning
confidence: 99%